Segregated Schools and the Mobility Hypothesis: A Model of Local Government Discrimination - Margo, R. A. (Quarterly Journal of Economics, 1991)
Around the turn of the century, Southern blacks lost the right to vote, and discrimination against them by local government officials intensified. This paper argues that, in the case of the de jure segregated public schools attended by black children, the ability of Southern blacks to "vote with their feet" placed limits on local government discrimination.